Preclinical assessment of a new live attenuated Mycobacterium tuberculosis Beijing-based vaccine for tuberculosis. Issue 6 (5th February 2020) - Levillain, Florence; Kim, Hongmin; Woong Kwon, Kee; Clark, Simon; Cia, Felipe; Malaga, Wladimir; Lanni, Faye; Brodin, Priscille; Gicquel, Brigitte; Guilhot, Christophe; Bancroft, Gregory J.; Williams, Ann; et al.
Abstract: Tuberculosis still claims more lives than any other pathogen, and a vaccine better than BCG is urgently needed. One of the challenges for novel TB vaccines is to protect against all Mycobacterium tuberculosis lineages, including the most virulent ones, such as the Beijing lineage. Here we developed a live attenuated M. tuberculosis mutant derived from GC1237, a Beijing strain responsible for tuberculosis outbreaks in the Canary Islands. The mutant strain is inactivated both in the Rv1503c gene, responsible for surface glycolipid synthesis, and in the two-component global regulator PhoPR. This double mutant is as safe as BCG in immunodeficient SCID mice. In immune-competent mice and guinea pigs, the mutant is as protective as BCG against M. tuberculosis strains of common lineage 4 (Euro-American). By contrast, in mice the vaccine is protective against a M. tuberculosis strain of lineage 2 (East-Asian, Beijing), while BCG is not. These results highlight differences in protection efficacy of live attenuated M. tuberculosis -derived vaccine candidates depending on their genetic background, and provide insights for the development of novel live vaccines against TB, especially in East-Asian countries where M. tuberculosis strains of the Beijing family are highly dominant.